VDAC3 As a Potential Marker of Mitochondrial Status Is Involved in Cancer and Pathology - Reina, Simona; Guarino, Francesca; Magrì, Andrea; De Pinto, Vito (Frontiers in Oncology, 2016)
VDAC3 is the least known isoform of the mammalian Voltage-Dependent Anion selective channels of the outer mitochondrial membrane. It has been recently shown that cysteine residues of VDAC3 are found over-oxidized. The VDAC3 cysteine over-oxidation was associated with the oxidizing environment and the abundance of ROS in the intermembrane space. In this work, we have examined the role of VDAC3 in general pathogenic mechanisms at the basis of mitochondrial dysfunction and involving the mitochondrial quality control. Many of the diseases reported here, including cancer and viral infections, are often associated with significant changes in the intracellular redox state. In this sense, VDAC3 bearing oxidative modifications can be considered marker of the oxidative load in the mitochondria and part of the ROS signaling pathway.